2021
DOI: 10.1093/brain/awab014
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to the Caspr1/contactin-1 complex in chronic inflammatory demyelinating polyradiculoneuropathy

Abstract: Previous studies have described the clinical, serological and pathological features of patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) and antibodies directed against the paranodal proteins neurofascin-155, contactin-1 (CNTN1), contactin-associated protein-1 (Caspr1), or nodal forms of neurofascin. Such antibodies are useful for diagnosis and potentially treatment selection. However, antibodies targeting Caspr1 only or the Caspr1/CNTN1 complex have been reported in few patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
87
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(93 citation statements)
references
References 39 publications
5
87
0
1
Order By: Relevance
“…Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is a clinically and pathologically diverse autoimmune syndrome of the peripheral nervous system, causing significant disability. 1 , 2 Disease-specific antibodies targeting proteins at the node and paranode of Ranvier, such as neurofascin 155 (NF155), 3 nodal neurofascins (NF186 and NF140), 4 contactin-1 (CNTN1), 5 or CNTN-1/caspr-1, 6 , 7 have been described in small subsets of patients with CIDP sharing immunopathologic mechanisms, clinical features, and treatment response and differing from those of typical CIDP. 8 , 9 This has led to the appearance of the autoimmune nodopathy (AN) diagnostic category in the recent update of the European Academy of Neurology/Peripheral Nerve Society CIDP diagnostic guidelines.…”
mentioning
confidence: 99%
“…Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) is a clinically and pathologically diverse autoimmune syndrome of the peripheral nervous system, causing significant disability. 1 , 2 Disease-specific antibodies targeting proteins at the node and paranode of Ranvier, such as neurofascin 155 (NF155), 3 nodal neurofascins (NF186 and NF140), 4 contactin-1 (CNTN1), 5 or CNTN-1/caspr-1, 6 , 7 have been described in small subsets of patients with CIDP sharing immunopathologic mechanisms, clinical features, and treatment response and differing from those of typical CIDP. 8 , 9 This has led to the appearance of the autoimmune nodopathy (AN) diagnostic category in the recent update of the European Academy of Neurology/Peripheral Nerve Society CIDP diagnostic guidelines.…”
mentioning
confidence: 99%
“…Recently, our group, in collaboration with others, has published a study analyzing the clinical and immunological characteristics of 15 AN patients with antibodies against the CASPR1/CNTN1 complex. We observed that patients presented with a rapid onset neuropathy with cranial nerve involvement, early axonal damage, and poor response to IVIg demonstrated that these antibodies target primarily CASPR1 protein, but binding is stronger when CNTN1 is also present [49]. Pathogenicity of these autoantibodies remains to be confirmed.…”
Section: Anti-caspr1/cntn1 Complex Antibodiesmentioning
confidence: 86%
“…A breakthrough in CIDP antibody autoimmunity has been the remarkable observation that a subset of patients who do not respond to IVIg or plasmapheresis have IgG4 antibodies to nodal/paranodal antigens directed against neurofascin-155 (Nfasc155), neurofascin-140/186 (Nfasc140/186), contactin-1 (CNTN1), and contactin-associated protein 1 (Caspr1) [1,7,[15][16][17][18][19]. These IgG4 antibodies form a clinicopathologically distinct CIDP subset, comprising 10% of all CIDP patients, often referred to as autoimmune nodopathies [20].…”
Section: Cidp With Paranodal Antibodiesmentioning
confidence: 99%
“…These IgG4 antibodies form a clinicopathologically distinct CIDP subset, comprising 10% of all CIDP patients, often referred to as autoimmune nodopathies [20]. Most commonly, CIDP nodopathies are associated with anti-Nfasc155, followed by Caspr1 and CNTN1, and rarely against both Nfasc140/186 and Nfasc155 [1,7,[15][16][17][18][19][20][21][22]. In contrast to common CIDP characterized by macrophagemediated demyelination, complement activation and myelin destruction, in patients with CIDP nodopathy, except of rare exceptions, the IgG4 nodal/paranodal antibodies do not cause macrophage activation and demyelination, do not fix complement to internalize specific nodal/paranodal antigens, and do not elicit an inflammatory response; instead, they affect protein-protein interaction exerting a functional blockade by disrupting the paranodal axoglial contact leading to conduction failure [1,7,[18][19][20][21].…”
Section: Cidp With Paranodal Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation